Effect of Aerobic-Based Exercise on Psychological Well-Being and Quality of Life Among Older People: A Middle East Study - Amir Shams; Hadi Nobari; Hadi Nobari; Hadi Nobari; José Afonso; Hamed Abbasi; Elena Mainer-Pardos; Jorge Pérez-Gómez; Mahdi Bayati; Alireza Bahrami; Lara Carneiro; Lara Carneiro (Frontiers Media S.A., 2021)
The aimed to evaluate the effects of low and moderate-intensity aerobic exercise on psychological well-being (PWB) and quality of life (QoL) among older people. Forty-five male Iranian adults aged 65-80 years were selected according to the eligibility criteria and randomly assigned to a low-intensity group (LIG) (40-50% of maximum heart rate), moderate-intensity group (MIG) (60-70% of maximum heart rate) and control group (CG). The exercise protocols consisted of 12 weeks of aerobic exercise (two sessions per week). Psychological well-being and QoL were assessed through the Ryff's Psychological Well-being Scale and the World Health Organization QoL Questionnaire. The statistical analysis for psychological well-being indicated that a significant main group (between-group) (F = 11.777, p < 0.001, ηp2 = 0.359), time (within-group) (F = 58.983, p < 0.001, ηp2 = 0.584) and interaction effect (group × time) (F = 20.146, p < 0.001, ηp2 = 0.490) for PWB total score. Bonferroni post-hoc tests revealed that the PWB total score in the MIG group was more significant than both LIG (p = 0.003) and CG (p < 0.001). Results for PWB components including self-acceptance, positive relationships with others, autonomy, purposeful life, and environmental mastery revealed no significant differences (p > 0.05). While there was a significant difference between the groups for personal growth component. Bonferroni post-hoc tests revealed that the personal growth in the MIG group was more significant than both LIG (p = 0.028) and CG (p < 0.001). Result for QoL indicated significant differences for the main group (F = 13.277, p < 0.001, ηp2 = 0.387), time (F = 25.533, p < 0.001, ηp2 = 0.378) and interaction effect (F = 9.992, p < 0.001, ηp2 = 0.332) for QoL total scale. Bonferroni post-hoc tests revealed that the QoL total scale in the MIG group was more significant than both LIG (p = 0.003) and CG (p < 0.001). Results for QoL components including Physical health, Social relationships, Health environment revealed no significant differences (p > 0.05), while there was a significant difference between the groups for the Psychological health component. Bonferroni post-hoc tests revealed that the Psychological health in the MIG group was more significant than both LIG (p = 0.009) and CG (p = 0.002). Therefore, aerobic exercise improves PWB and QoL in older adults, moderate-intensity exercise seems to produce higher benefits than low-intensity, demonstrating a positive dose-response relationship.